MENTAL ACTIVITY RESTORATION PECULIARITIES IN CHILDREN WITH SEVERE TRAUMATIC BRAIN INJURY AT THE EARLY STAGE OF REHABILITATION - A. V. Zakrepina (Педиатрическая фармакология)
The article is concerned with rehabilitation issues of children with severe traumatic brain injury (STBI). It gives the results of the study which was aimed at analyzing the psychophysical health restoration dynamics in children with STBI and determining the pedagogic typology of deviant development at traumatic brain injury in order to devise a training-organizational work plan for children being on the stages of complex rehabilitation.